Denaturation of whey proteins of milk during ohmic heating - Pereira, Ricardo (2010)
Ohmic heating has often been said to improve the sensorial quality of foodstuffs, which has been ttributed mainly to its volumetric heating mechanism and (eventually) to the presence of an electric field. This is still subject to doubts and questions from the scientific community, and it is therefore important to determine the effect of ohmic heating on food constituents. We have investigated whether ohmic heating technology would give rise to changes on the denaturation of whey proteins from bovine milk. Whey protein solutions samples were heated at 85 ºC (up to 30 min) and ohmic heating experiments were also adapted to simulate the sample temperature changes during conventional (indirect heating) experiments. Our results show that ohmic heating seems to reduce protein unfolding and denaturation, when compared with conventional heating.